Structural Equation Modeling of Green Economy Outcomes in Thailand’s Manufacturing Industry - Lalaeng , Chanyaphak; Hongsakul, Bharis (Journal of Ecohumanism, 2024)
This research aimed to analyze the causal relationship model and outcomes of the Green Economy in Thailand’s manufacturing industry. Data was collected through a questionnaire targeting small and medium enterprise (SME) operators in the Thai textile manufacturing industry, who are registered as legal entities and SME members. The statistical analysis involved confirmatory factor analysis (CFA) and structural equation modeling (SEM). The major findings revealed that the structural model was well-aligned with the empirical data. The study demonstrated that the Green Economy, market effectiveness, and competitive advantage all had significant positive effects on business performance. Further analysis showed that the Green Economy directly influenced market pressures and competitive advantage. Additionally, the study identified positive direct relationships between market pressures, green dynamic capabilities, and socially responsible leadership with the Green Economy.